2015
DOI: 10.4028/www.scientific.net/amm.772.424
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Downsizing - A Critical Analysis of the Limits of the Agile Flying Wing MiniUAV

Abstract: The missions of small flying wing UAVs require maneuver capabilities as well as optimal flight performance to balance the low operating and manufacturing costs. The basic principles in designing aviation structures must be readjusted due to the innovative concepts regarding the use of advanced materials as well as to the perspectives of using alternative energy aboard UAVs. The current paper is a synthesis of the 2D and 3D aerodynamic analysis of small swept flying wing UAVs that offers a global image of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…On the other hand, at the angles of attack accompanying the stall, a much larger angle can be noticed that is needed to lose the lift in relation to the LS model [27]. The PD model, on the other hand, excels here with a very high value (24.7 • -marked with the green circle in Figure 10).…”
Section: The Specificity Of the Flight Phases Of The Flatflyer Modelmentioning
confidence: 94%
“…On the other hand, at the angles of attack accompanying the stall, a much larger angle can be noticed that is needed to lose the lift in relation to the LS model [27]. The PD model, on the other hand, excels here with a very high value (24.7 • -marked with the green circle in Figure 10).…”
Section: The Specificity Of the Flight Phases Of The Flatflyer Modelmentioning
confidence: 94%
“…To analyze the maneuver control in gliding/soaring flight (without wings flapping) initial conditions for aerodynamic simulation are required for characteristic angles of the lifting surfaces (eg: the dihedral angle of the wing, lateral and longitudinal angles of the tail assembly/tail). Validation of the results with free software tools should be compared with commercial CFD codes (i.e., Solidworks-Floworks, Ansys-Fluent) which provide a high degree of confidence on the pre-processing and post-processing data analysis, [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Mokhtar [6] conducted a parametric study of high-lift airfoils including the Eppler E423, Douglas/Liebeck LNV109A, NACA 9315 and Selig S1223, and proposed a new WM004 airfoil section. Prisacariu [7] used Easy CFD software to analyze the Phoenix, Clark YH, and MH91 airfoils for flying wings. Dinh et al [8] concluded that the TL54 airfoil provides superior aerodynamic performance based on a collection of low-speed FW UAV airfoil series (Eppler, MH, HS series etc.).…”
Section: Introductionmentioning
confidence: 99%